Pengaruh Kualitas Layanan, Prosedur Kredit, Suku Bunga Kredit dan Program Pengembangan Kapasitas Usaha Terhadap Keputusan Pengambilan Kredit Mikro di Masa Pandemi Covid 19 - Fitroh Ramadhan; Iman Murtono Soenhadji (Universitas Katolik Soegijapranata, Semarang, 2023)
Micro credit is a facility provided by the government through financing or capital institutions to finance or provide loans to business actors who meet the criteria as Micro, Small and Medium Enterprises (MSMEs) in accordance with Law no. 20 of 2008 concerning Micro, Small and Medium Enterprises. With the availability of access to financing for SMEs, one of which is PT. Madani National Capital (PNM) which until 2021 the number of customers is 11.6 million throughout Indonesia. Based on this, this study aims to analyze the effect of service quality, credit procedures, loan interest rates and business capacity development programs on credit making decisions during the Covid-19 pandemic, either partially or simultaneously. The primary data obtained from respondents who are customers of PANTAS products are 70 respondents through a research instrument in the form of a questionnaire that has passed validity and reliability tests. Data were analyzed using the RLB or Multiple Linear Regression method. The results of this study indicate that the variables of service quality, credit procedures and business capacity development programs have a significant effect on customer decisions in making credit, while loan interest rates have no significant effect and partially significant influence on micro decision making with an influence level of 73.9 percent.